2017
DOI: 10.5901/jesr.2017.v7n2p9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Revised Two-Factor Study Process Questionnaire (R-SPQ-2F) for Student Teacher Approaches to Learning

Abstract: A deep approach to learning is essential for student academic achievement and several studies demonstrate a significant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
3
13
0
Order By: Relevance
“…Findings show that students use the deep approach than the surface approach although additional statistics suggests that the students might have employed both approaches in the study of Economics. This finding is consistent with that of Martinelli and Raykov (2017) which reported that overall students' scores for the deep and surface approaches are invariant in regard to gender and the year of study with high scores consistently reported for the deep approach compared with the surface approach. The present findings corroborates the assertion made by Entwistle et al (1979) that deep and surface approaches had developed into fairly regular interconnected learning behaviours as these approaches were apparent simultaneously across different learning tasks.…”
Section: Discussion Of Findingssupporting
confidence: 90%
See 2 more Smart Citations
“…Findings show that students use the deep approach than the surface approach although additional statistics suggests that the students might have employed both approaches in the study of Economics. This finding is consistent with that of Martinelli and Raykov (2017) which reported that overall students' scores for the deep and surface approaches are invariant in regard to gender and the year of study with high scores consistently reported for the deep approach compared with the surface approach. The present findings corroborates the assertion made by Entwistle et al (1979) that deep and surface approaches had developed into fairly regular interconnected learning behaviours as these approaches were apparent simultaneously across different learning tasks.…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…Shah et al (2006) established internal consistency co-efficients ranging from 0.71 to 0.72 from a sample of medical students in Nepal. Martinelli and Raykov (2017) indicated acceptable internal consistency coefficients of 0.73 and 0.75 for deep and surface approaches, respectively, using Cronbach's Alpha in a sample of prospective teachers, while Tasdemir et al (2014) established Cronbach alpha values of 0.79 for the deep approach and 0.74 for the surface approach from a sample of prospective teachers in Turkey. For the present study, Cronbach Alpha values of 0.86 and 0.75 for deep and surface approaches, respectively, were established.…”
Section: The Revised Two Factor Study Process Questionnaire (R-spq-2f)mentioning
confidence: 96%
See 1 more Smart Citation
“…Hence, this study aimed to know the learning approach of second-year undergraduate medical students using the Revised Two Factor Study Process Questionnaire (R-SPQ-2F) and determine the presence of any correlation between the surface or deep approach to learning, the marks obtained in pharmacology sessional and university examinations, and the presence of any gender difference. The R-SPQ-2F has been shown to be a reliable tool to determine the student learning approaches [7]. We hypothesized that students with a deep learning approach would perform better in the examinations compared with those with a superficial approach.…”
Section: Introductionmentioning
confidence: 99%
“…Such facets were Surface Motive, Surface Strategy, Deep Motive, Deep Strategy (Biggs, 1987). obtaining good psychometric indicators (Freiberg-Hoffmann & Fernández-Liporace, 2016;Khine & Afari, 2018;Martinelli & Raykov, 2017;Merino-Soto & Kumar-Pradhan, 2013;Sohrabi, 2016;Vergara-Hernández, Simancas-Pallares, & Carbonell-Muñoz, 2019;Zakariya, Bjørkestøl, Nilsen, Goodchild, & Lorås, 2020). Furthermore, Leung (2006) replicated the two-dimension structure in five samples of students from different countries -USA, Australia, Hong Kong, Macao, and the United Kingdom.…”
Section: Introductionmentioning
confidence: 98%